SOLEDGE3X integrated core-edge modelling of tungsten sources, migration, and radiation in WEST plasmas - N. Varadarajan; H. Bufferand; G. Ciraolo; L. Cappelli; P. Tamain; N. Rivals; S. Sureshkumar; V. Quadri; L. de Gianni (Nuclear Materials and Energy)
The W impurity species was introduced in the multi-component edge fluid code SOLEDGE3X, in its 2D transport version. To do so, several physical ingredients have been implemented. Firstly, W gross erosion is calculated using the Garcia-Rosales formula, and W re-deposition is estimated with either a Groth–Tskhakaya formulation or a Neural Network trained on re-deposition data from a kinetic model. This fluid approach for W transport is compared with kinetic results obtained with ERO2.0 in edge and SOL domains. Moreover, as W radiates mainly in the core region, which was thus far not resolved in SOLEDGE3X, a 1D model has been implemented for the core plasma region assuming poloidal symmetry. The impact of Oxygen impurities on W content is also addressed (including in particular the impact of W oxide layers on the PFCs). A few applications of the model implementing a Deuterium plasma with Oxygen and Tungsten, taking into account the sputtering of Tungsten by Oxygen are shown.